Application of Advanced Oxidations Processes for the Treatments of Textile Effluents - Bilal, Nasir; Ali, Shaukat; Iqbal, Munawar (Asian Journal of Chemistry, 2014)
The effect of various advanced oxidation processes (FeSO4/H2O2, FeSO4/H2O2/UV, KMnO4, TiO2/H2O2/UV, TiO2/H2O2/dark, H2O2 /UV, H2O2/dark and sunlight) was compared for the treatment of textile wastewater on the basis of chemical oxygen demand (COD), total organic carbon (TOC), total suspended solids (TSS), dissolved oxygen (DO), phenolics and decolourization. Fenton and photofenton treatment showed highest effect on COD, TOC, TSS and colour reduction, while KMnO4 showed 80-85, 45-50 and 20-30 %, reduction in colour, COD and TOC, respectively. The reduction in COD, TOC and colour using TiO2/UV was found to be 75-85, 65-70 and 85-95 %, respectively and TiO2 in dark and sunlight did not showed appreciable effect on water quality parameters versus Fenton, KMnO4 and TiO2/UV. The percentage effect of H2O2/UV on colour and COD was 80-85 and 40-45 % and H2O2/dark showed 20-25, 10-15 and 45-55 % reduction in COD, TOC and colour, respectively. The mineralization was recorded 95 and 80 % for Fenton and KMnO4 for 6 h of treatment. Results showed that the advanced oxidation processes have promising effect to improve water quality and could be employed for wastewater treatment.